Hidden exploitation of women’s care work in Indonesia’s gig economy - Syamsu Budyanti; Surokim (C-DISC, 2026)
The rapid expansion of Indonesia’s digital economy has positioned the gig economy as a pathway for women’s economic inclusion through flexible, home-based digital work. However, this narrative often obscures the structural inequalities embedded in platform-based labor systems. This study examines how women’s digital labor intersects with unpaid care work to produce invisible, gendered forms of exploitation. Employing a qualitative case study approach, the research was conducted in the Greater Malang area of Indonesia and involved 15 women engaged in online selling, affiliate marketing, and content creation. Data were collected through in-depth interviews, limited observation, and digital documentation, and analyzed using thematic analysis informed by intersectionality and social reproduction perspectives. The findings reveal that women simultaneously perform domestic, digital, and emotional labor within blurred temporal boundaries. Rather than providing genuine flexibility, the gig economy operates through pseudo-flexibility characterized by algorithmic control, unstable income an always-on work culture, and limited social protection. Women’s digital labor remains socially undervalued, reinforcing unequal household power relations and perpetuating the invisibility of gendered labor. The study argues that the gig economy functions as a regime of invisible gendered labor in which technological infrastructures and patriarchal social structures mutually reproduce inequality through subtle yet exploitative mechanisms.